Pivotal Considerations for Optimal Deployment of Healthy Volunteers in Oncology Drug Development - Mariam A. Ahmed; Chirag Patel; Nicole Drezner; Whitney Helms; Weiwei Tan; Daria Stypinski (Wiley, 2020)
Oncology drug development is among the most challenging of any therapeutic area, with first‐in‐human trials expected to deliver information on both safety and activity. Until recently, therapeutic approaches in oncology focused on cytotoxic chemotherapy agents, ruling out even the possibility of enrolling normal healthy volunteers (NHVs) in clinical trials due to safety considerations. The emergence of noncytotoxic modalities, including molecularly targeted agents with more favorable safety profiles, however, has led to increasing numbers of clinical pharmacology studies of these agents being conducted in NHVs. Beyond rapid enrollment and cost savings, there are other advantages of conducting specific types of studies in NHVs with the goal of more appropriate dosing decisions in certain subsets of the intended patient populations, allowing for enrollment of such patients in therapeutic trials from which they might otherwise have been excluded. Nevertheless, the decision must be carefully weighed against potential disadvantages, and although the considerations surrounding conduct of clinical trials using NHVs are generally well‐defined in most other therapeutic areas, they are less well‐defined in oncology.